ABC END VEN ANALYSYS OF COSTS FOR MEDICINE SAND MEDICAL TREATMENT COSTS PATIENT - M. A. Shapovalova; L. R. Koretskaya (IRBIS LLC, 2015)
Abstract: for a detailed assessment of neurological patients to assist non-governmental agencies in Health Departmental Hospital station Astrahan 1 «Russian Railways», we carried out ABC and VEN analysis of pharmacotherapy and medical services in the department of neurology. An assessment of the costs of hospitalization, medication, medical services.